Re-irradiation for head and neck cancer: outcome and toxicity analysis using a prospective single institution database - Scolari, Chiara; Buchali, André; Franzen, Achim; Förster, Robert; Windisch, Paul; Bodis, Stephan; Zwahlen, Daniel R.; Schröder, Christina (Frontiers in Oncology, 2023)
Purpose: Decisions on benefit-risk balance for re-irradiation (re-RT) in head and neck cancer remain challenging. Prospectively collected data on this topic are rare. In this study, we aimed to explore the feasibility of re-RT in patients with loco-regionally recurrent or second primary head and neck cancer (LRR/SP HNC) using a prospectively established database. Methods: Sixty-one LRR/SP HNC patients treated with re-RT between 2004 and 2021 were included. Re-RT was defined as having a second course of RT with curative intent resulting in a cumulative dose of ≥100 Gy in an overlapping volume. For the entire patient cohort, the same treatment protocol and techniques were used: postoperative or definitive dynamic intensity-modulated and/or volumetric modulated re-RT administered using twice daily hyperfractionation (total dose of 60 Gy) combined with cisplatin or carboplatin plus 5-fluorouracil. Overall survival (OS), progression-free survival (PFS), locoregional control (LRC) and distant metastasis control (DMC) were analyzed and prognostic factors evaluated. Toxicity was prospectively recorded and graded. Results: The median follow-up was 9.8 months. In forty-one patients (67.1%), the complete administration of the intended treatment was not possible. Two-year OS, PFS and LRC rates were 19%, 18% and 30%, respectively. In the 20 patients (33%) receiving the complete intended treatment, 1- and 2-year OS rates were 70% and 47%, respectively. Multivariate analysis revealed recurrent N stage 0–1, younger age, chemotherapy administration and re-RT dose of 60 Gy as significantly favorable factors for clinical outcomes. No grade 5 re-RT-related toxicity was observed. The most common new grade ≥3 acute toxicities were dysphagia (52%) and mucositis (46%). Late toxicity included grade ≥3 dysphagia in 5% of evaluable patients and osteoradionecrosis in 10%. Six patients (10%) were still alive after nine years, presented neither locoregional nor distant progression and, except for osteoradionecrosis in two patients, no late toxicity grade ≥3 was observed. Conclusions: The present analysis demonstrated that hyperfractionated re-RT with 60 Gy plus platinum-based chemotherapy was a curative treatment option with acceptable prospectively graded toxicity in LRR/SP patients. However, patients for whom chemotherapy was not possible, derived unsatisfactory benefits from re-RT, highlighting the importance of patient selection fit for chemo-re-RT.